Psychological teleassistance for university students with Autism Spectrum Disorder with anxiety, depression and psychotic episodes in times of COVID-19 - Aldazábal Contreras, Ana (2020)
The Autism spectrum disorder is considered as a group of gradation in the social behave, communication, language and the stereotype of interest and restricted activities. This condition is co-occurring to psychological affections. Psychological teleassistance has been a powerful tool during the COVID19 Pandemic. The purpose of this study was to describe the procedure and function of the Psychological teleassistance to Autism university students who suffer anxiety, depression and psychotic episodes, describing the process, showing the strategies, techniques, tools and all technological resources, also to establish the benefits and limits to make an excellent attention online. The study was descriptive, the sample was made up of 10 university students diagnosed with Autism from a private higher educational institution in Lima. The Psychological Teleassistance allowed identifying the causes of the occurrence of critical episodes that were grouped into typical factors and factors that are related to the symptoms of autism, proved to be a useful resource because it allowed identifying needs, establishing an online database, applying techniques adapted from cognitive behavioral therapy remotely, and include parents. It was concluded that Psychological Teleassistance requires assessment instruments adapted to the condition, in addition, it can be applied in different settings and with different modalities, contributing to the future development of skills for the autistic population.